MENGANALISA FAKTOR-FAKTOR YANG MEMEPENGARUHI KUALITAS PELAYANAN MENGGUNAKAN QUALITY FUNCTION DEPLOYMENT DI APOTEK XYZ - Safari, Ibrahim; Nova lumbanraja, Vera; Susiyanto, Hendro (Universitas Krisnadwipayana, 2024)
The development of pharmacies to be able to meet consumer needs is increasing, one of which is the XYZ Pharmacy. This case study aims to analyze the factors that influence service quality at XYZ Pharmacy, especially at XYZ Pharmacy Pos Pengumben. The use of the QFD method in this study can improve and improve the quality of service at XYZ Pengumben Post. From the research it can be determined that the factors that influence service quality at XYZ Pos Pengumben Pharmacy are the top priority for consumers regarding service quality in the HOQ, namely: adequate and complete pharmacy facilities, easy service procedures, neat and clean spatial arrangement, the service ability of staff serving customers, the discipline of pharmacy staff, following up on criticism and suggestions received, evaluating the performance of pharmacy employees every month, service to all consumers regardless of social status, computerization of the payment system, product prices and the completeness of various kinds of medicines.